#2**+2 **

\({x \choose y}=\frac{x!}{y!(x-y)!}\)

Knowing this formula will allow you to compute any input for the choose function. Now, let's compute the result.

\({7 \choose 6}=\frac{7!}{6!*(7-6)!}\) | Let's simplify the denominator first. |

\(\frac{7!}{6!*(7-6)!}=\frac{7!}{6!}\) | In order to simplify this, let's think about it this way... |

\(\frac{7!}{6!}=\frac{7*6*5*...*1}{\hspace{3mm}6*5*...*1}\) | There is a lot that will cancel here. |

\(7\) | |

TheXSquaredFactor
Oct 19, 2017

#2**+2 **

Best Answer

\({x \choose y}=\frac{x!}{y!(x-y)!}\)

Knowing this formula will allow you to compute any input for the choose function. Now, let's compute the result.

\({7 \choose 6}=\frac{7!}{6!*(7-6)!}\) | Let's simplify the denominator first. |

\(\frac{7!}{6!*(7-6)!}=\frac{7!}{6!}\) | In order to simplify this, let's think about it this way... |

\(\frac{7!}{6!}=\frac{7*6*5*...*1}{\hspace{3mm}6*5*...*1}\) | There is a lot that will cancel here. |

\(7\) | |

TheXSquaredFactor
Oct 19, 2017